Efficacy of Nigerian Local Honey on Pseudomonas Aeruginosa from Infected Wound among Genders in Federal Medical Center, Bayelsa - Olorode , Oluwayemisi A.; Godswill , Benson Azibanamughon (Jour Med Resh and Health Sci, 2023)
Honey, a natural product can be used as a sweetening and as well as an antimicrobial agent in most parts of the world and it is generally believed that it is a wound healer. This work was carried out between February and April 2022 to assess the antimicrobial effectiveness of Nigerian honey on the Pseudomonas aeruginosa associated with the wound infection. The Infected wound samples collected from fifty (50) patients from Federal Medical Centre, Yenagoa were cultured on Nutrient agar and further confirmed on Cetrimide agar and characterized by standard microbiology techniques. Undiluted isolated Pseudomonas aeruginosa strains standardized by 0.5 Mac Farland standard turbidity solution was tested different concentrations (20%, 40%, 60%, 80%, 100%) of Nigeria locally produced honey purchased from Tombia main market, Bayelsa State using cork borer agar diffusion method; this was incubated for 24 hrs for the expression of the zone of inhibition. Findings showed that out of 50(100%) wound samples examined, 15 (30%) were positive for Pseudomonas aeruginosa. From the statistical calculation, observation showed no significant difference in the frequency of Pseudomonas aeruginosa among genders at p=0.955 and age group examined at p value of 0.08. Likewise, the combination statistical analysis for both gender and age had no difference significantly in the prevalence of the isolated strains of Pseudomonas organism at P value of 0.27. Of all the concentrations of honey used against these strains, there was no zone of inhibition to be measured amounting to lack of potency of this product on Pseudomonas aeruginosa. In conclusion, locally made honey in the Niger Delta region of Nigeria is not effective against Pseudomonas aeruginosa associated with wound infection in this region therefore it should not be used as a wound healer due to its ineffectiveness. Further research should be done by carrying out the phyto-chemical analysis of Nigeria locally produced honey especially in the Niger Delta region of Nigeria to confirm its authenticity and the use of spectrophotometer machine for analyzing the effectiveness of honey could be significant.